Anti-neuropathic effects of astaxanthin in a rat model of chronic constriction injury: passing through opioid/benzodiazepine receptors and relevance to its antioxidant and anti-inflammatory effects - Hashemi, Boshra; Fakhri, Sajad; Kiani, Amir; Abbaszadeh, Fatemeh; Miraghaee, Shahram; Mohammadi, Mohammad; Echeverría, Javier (Frontiers in Pharmacology, 2024)
Neuropathic pain is a debilitating neurological disorder and is on the rise. Since no effective treatment has been so far approved to combat the complex pathological mechanisms behind neuropathic pain, finding new therapeutic candidates is of great importance. Astaxanthin (AST) is a carotenoid with strong antioxidant, and anti-inflammatory activities. The present research aimed to evaluate the ameliorative effects of AST on a rat model of neuropathic pain.To induce neuropathic pain, a chronic constriction injury (CCI) model was employed.Accordingly, Wistar rats were divided into nine groups of six including sham, negative control group (CCI), positive control group gabapentin (100 mg/kg), AST (5, 10 mg/kg), flumazenil (0.5 mg/kg), naloxone (0.1 mg/kg), AST (10 mg/kg) + flumazenil (0.5 mg/kg), and AST (10 mg/kg) + naloxone (0.1 mg/kg) were administered intraperitoneally on days 1, 3, 5, 7, 10, and 14. To check the experimental signs of neuropathic pain and motor dysfunction, hot plate, acetone drop, and open field tests were used at the same time points. Additionally, biochemical assay and zymography were done on days 7 and 14 to assess the changes in catalase, glutathione and nitrite, as well as matrix metalloproteinases (MMP-2 and MMP-9). Besides, histological evaluations were performed for tissue damages on days 7 and 14.Results indicated that intraperitoneal injection of AST improved allodynia, hyperalgesia, and locomotor activity after CCI. AST also increased catalase and glutathione while suppressing nitrite, MMP-2, and MMP-9 activity through opioid/benzodiazepine receptors.The results highlighted AST as a promising candidate against neuropathic pain with beneficial effects on motor function by suppressing inflammatory mediators, and augmenting antioxidant factors, passing through opioid/benzodiazepine receptors.